E-Peer Assisted Learning Strategies (e-PALS) – Opportunities, Challenges and Way forward - Rajesh Perumbilavil Kaithamanakallam; Bharathi Sengodan; Gokulshankar Sabesan (Asian Journal of Medicine & Health Sciences, 2021)
Background: Peer-assisted learning strategies (PALs) is an excellent teaching-learning process. Negating the dominant facilitator’s role is a significant advantage of PALs over Problem based learning (PBL). With the moderators being their peers themselves, learners are not scared to make mistakes and participate in active discussions. This paper explains how technology can solve the common problems encountered during Peer Assisted Learning Strategies (PALs).WhatsApp’s abundant features like sending text messages, images, Graphics Interchange Format (GIFs), videos, documents, user location, audio files, phone contacts, and voice notes make it an ideal tool in medical education and application in e-PALs. Methods: The session begins by grouping the participants into small teams. The distribution of the PALs material to the groups is followed by discussing their specific material within their respective group and then discussing it in the plenary with all the other groups taking turns to present their material. Pre and post-tests allowed evaluation of the effectiveness of collaborative group work in e-PALs using WhatsApp. Each group, comprising the participants and the peer tutor, discusses their specific content in their small teams. The teams join together for the plenary and start the session by introducing their parasitic title as an icebreaker. Following the icebreaking, each team share their content in the plenary. Participation in the PALs sessions is purely voluntary, and the students are free to leave the WhatsApp group in case of any discomfort.